Mediating the Worst of Both Worlds effect with facets of criminal thought process: moral neutralization, cognitive impulsivity, and their interaction - Walters, Glenn D. (Deviant behavior, 2023)
The Worst of Both Worlds (WBW) hypothesis holds that prior offending and substance use in combination is significantly more likely to lead to antisocial behavior than either prior offending or prior substance use alone. In an effort to better understand the mechanisms behind the WBW effect, we performed a causal mediation analysis in which moral neutralization and cognitive impulsivity served as mediators of the WBW-delinquency relationship in a group of 845 (406 boys, 439 girls) early adolescents. We then tested the indirect effect for each pathway using longitudinal data and bias-corrected bootstrapped confidence intervals. Results showed that moral neutralization, but not cognitive impulsivity or the neutralization x impulsivity interaction, mediated the relationship between WBW and delinquency. These findings indicate that moral neutralization may play a salient role in the WBW effect by linking offending-substance comorbidity to future antisocial behavior. There is a need for additional research, however, to ascertain how and why comorbid criminal offending and substance use/abuse link specifically to moral neutralization, whereas there appears to be no connection between crime-substance comorbidity and cognitive impulsivity.